Analysis of Agrarian Transformation Research - Selçuk, Mustafa; Wijaya, Junior Hendri (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2024)
Research on Agrarian Transformation is important because it touches on how a change or transformation occurs in the agricultural sector, which will also affect the condition of society. This research focuses on bibliometric analysis that seeks to analyze how research related to agrarian transformation is carried out. In this study, VOSviewer and Publish or Perish are used to facilitate data search and depiction. Data from the Scopus database is searched through Publish or Perish, with the keyword Agrarian Transformation. Furthermore, to visualize the data, VOSviewer version 1.6.19 is used to view network visualizations, overlays, and densities. The results showed that there were 7069 citations in all selected results, 706.90 citations per year, and 35.25 citations per paper. In addition, this study shows the 10 most influential authors in terms of the number of citations displayed. In network visualization, the networks that appear most often are land and production. The overlay visualization shows that before 2016 and after 2019, not much research or publication was done on the topic. Meanwhile, density visualization shows that the keywords that most often appear are agrarian transformation, transformation, agrarian change, development, land, and production, and agriculture. The limitation of this study is that the data is only taken through the Scopus database and the year of publication is taken only for ten years